Evaluating the success of IS/IT Projects: how are companies doing it? - Varajão, João (2018)
The article aims to contribute to a better understanding of project management practices concerned with the evaluation of the success of Information Systems (IS)/Information Technology (IT) projects. It describes an exploratory study that inquired ten companies regarding their practices of projects success valuation. Results show that regardless of company size, sector or adopted project management methodology, the evaluation of projects success is currently an informal and rudimentary process mainly focused on the success of project management and not on the success of the projects’ deliverables. Given the importance and complexity of the evaluation of projects' success, companies should define and implement systematic processes for success management aiming to improve project performance and expected benefits, and this seems not to be happening in practice.